Adolescent kratom exposure affects cognitive behaviours and brain metabolite profiles in Sprague-Dawley rats - Zul Aznal, Aiman Nadhirah; Mohamad Nor Hazalin, Nurul Aqmar; Hassan, Zurina; Mat, Noorul Hamizah; Chear, Nelson Jeng-Yeou; Teh, Lay Kek; Salleh, Mohd Zaki; Suhaimi, Farah Wahida (Frontiers in Pharmacology, 2022)
Adolescence is a critical developmental period during which exposure to psychoactive substances like kratom (Mitragyna speciosa) can cause long-lasting deleterious effects. Here, we evaluated the effects of mitragynine, the main alkaloid of kratom, and lyophilised kratom decoction (LKD) on cognitive behaviours and brain metabolite profiles in adolescent rats. Male Sprague-Dawley rats (Postnatal day, PND31) were given vehicle, morphine (5 mg/kg), mitragynine (3, 10, or 30 mg/kg), or LKD (equivalent dose of 30 mg/kg mitragynine) for 15 consecutive days. Later, a battery of behavioural testing was conducted, brain was extracted and metabolomic analysis was performed using LCMS-QTOF. The results showed that mitragynine did not affect the recognition memory in the novel object recognition task. In the social interaction task, morphine, mitragynine, and LKD caused a marked deficit in social behaviour, while in Morris water maze task, mitragynine and LKD only affected reference memory. Metabolomic analysis revealed distinct metabolite profiles of animals with different treatments. Several pathways that may be involved in the effects of kratom exposure include arachidonic acid, pantothenate and CoA, and tryptophan pathways, with several potential biomarkers identified. These findings suggest that adolescent kratom exposure can cause cognitive behavioural deficits that may be associated with changes in the brain metabolite profiles.